Skin material
A polyester-based skin material with thermoplastic resin bonding enhances abrasion resistance and luxury feel, addressing the limitations of existing artificial leather by ensuring recyclability and durability.
Patent Information
- Application Number
- JP2023111687
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-06
- Publication Date
- 2025-01-20
AI Technical Summary
Existing artificial leather materials lack sufficient abrasion resistance, luxurious appearance, and recyclability, often containing polyurethane that deteriorates over time and complicates recycling.
A skin material composed of a skin layer and a base material layer, both made of polyester fibers or resin, with a thermoplastic resin adhering between the fibers to enhance abrasion resistance and luxury feel, and a recyclable structure.
The material achieves high abrasion resistance, luxurious appearance, and is fully recyclable, suitable for various applications including car interiors and clothing, while avoiding polyurethane-related issues.
Smart Images

Figure 2025009002000001 
Figure 2025009002000002 
Figure 2025009002000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a skin material. [Background technology]
[0002] Artificial leather is widely accepted in the market as an alternative material to natural leather, and is widely used as a highly functional design material because it has been developed into a wide variety of products such as grain and suede, can be dyed to produce a wide variety of colors not found in natural leather, and is easy to maintain. In particular, suede-like artificial leather with a brushed outer surface is preferably used in fields such as shoes, bags, furniture, interior materials such as seat coverings for automobiles, railway vehicles, aircraft, and ships, and clothing materials such as ribbons and badge base materials. In these fields, there is a demand for a good appearance quality, a supple feel, and resistance to physical loads such as abrasion resistance for long-term use.
[0003] According to the definition of JIS-6601, artificial leathers are classified into "smooth" having a grain-like appearance of leather and "napped" having an appearance of nubuck, suede, velour, etc. of leather, depending on their appearance. The artificial leather of this embodiment relates to one classified as "napped" (i.e., brushed artificial leather having a brushed appearance). The brushed appearance can be formed by buffing (brushing) the outer surface (also called the front surface) of the main fiber layer with sandpaper or the like. In this specification, the outer surface of the artificial leather, the outer surface of the main fiber layer, the outer surface of the fiber sheet, and the outer surface of the laminated sheet are the surfaces exposed to the outside when used as artificial leather (for example, the surface that comes into contact with the human body in the case of chair use). In one embodiment, in the case of brushed artificial leather, the outer surface of the main fiber layer is brushed or raised by buffing or the like.
[0004] The mainstream of artificial leather materials is a nonwoven fabric structure made of entangled fibers made of materials such as polyethylene terephthalate and polyamide, impregnated with and attached to a polymeric elastomer resin such as polyurethane. If the fibers are simply left physically entangled by needle punching or hydroentanglement without being impregnated with a polymeric elastomer resin, the resulting product will have problems such as insufficient abrasion resistance during actual use, lacking the supple feel of artificial leather, and frequent shedding of threads during the dyeing process, which causes manufacturing defects.
[0005] Therefore, in the manufacturing process of artificial leather, a method of attaching a polymeric elastomer such as polyurethane to give it a good texture and abrasion resistance is widely used. For example, artificial leathers impregnated with polyurethane are commercially available under the names of Lamous (trademark), Ecsaine (trademark), Alcantara (trademark), etc. However, polymeric elastomers such as polyurethane have a high tendency to bleed out dyes, and if sufficient reduction washing treatment is not used, they tend to cause problems such as poor washing fastness, vulnerability to ultraviolet rays, and susceptibility to deterioration due to long-term use, resulting in color changes and deterioration during long-term use. In addition, since they cannot be decomposed under reaction conditions that cause polyester to depolymerize, recycling is difficult in a composite system with polyester fiber, which is the most widely used main fiber for artificial leather.
[0006] In the following Patent Document 1, in order to provide a nonwoven fabric for artificial leather that has good feel, high abrasion resistance, ease of cutting, and shape stability without impregnation with a polymer elastomer such as polyurethane resin, a nonwoven fabric for artificial leather is manufactured by mixing heat-fusible short fibers in a specific ratio at least in the surface fiber layer of a nonwoven fabric having a multilayer structure of at least two layers, a surface fiber layer and a scrim layer which is a woven or knitted fabric, and then subjecting the surface fiber layer to a heat fusion treatment. Applications of the nonwoven fabric include vehicle interior materials, but there is no mention of a substrate layer to be bonded to the nonwoven fabric for artificial leather.
[0007] In addition, in the following Patent Document 2, in the invention described in Patent Document 1, a part of the thermoplastic resin formed by melting the heat-fusible short fibers is exposed in the form of a lump of a specified size on the outer surface of the surface fiber layer, thereby improving abrasion resistance (40,000 times or more in an abrasion resistance test using the Martindale method) and feel (bending value of less than 24 cm in a KES pure bending test). However, like Patent Document 1, automotive interior materials are also listed as uses, but there is no mention of a substrate layer to be bonded to the nonwoven fabric for artificial leather.
[0008] By the way, skin materials are often composed of a skin layer, an adhesive layer, and a base layer. The base layer is used because the skin layer alone does not have sufficient mechanical properties, etc. The adhesive layer is necessary to bond the base layer and the skin layer. As described in the following Patent Document 3, semi-rigid polyurethane foam is often used for the base material layer of conventional vehicle seats. Even if only the skin layer is composed of polyester-based resin or fiber, if the adhesive layer and base material layer are similarly made of other materials, the skin material will be a composite material, making chemical recycling involving polyester depolymerization difficult.
[0009] The skin material is also used as a seat covering material. A vehicle seat is often made up of the seat covering material, a seat frame, and a seat pad. Providing a high-class appearance and texture to the seat covering material can impart a high-class appearance and texture to the vehicle seat. However, commercially available vehicle seats with a high-class appearance and texture often partially use synthetic leather such as PVC or natural leather, and semi-rigid polyurethane foam is often used in the base layer, making them a composite material that is not easy to recycle.
[0010] The skin material is also used as a vehicle seat cover. A vehicle seat cover is a seat cover that is detachably attached to a vehicle seat. By providing a high-class appearance and texture to the vehicle seat, the vehicle seat can also be given a high-class appearance and texture. In addition, a removable seat cover is easy to separate from the seat and is suitable for recycling. However, commercially available vehicle seat covers that have a high-class appearance and texture often partially use synthetic leather such as PVC or natural leather, and often use semi-rigid polyurethane foam in the base material layer, which makes them a composite material and therefore difficult to recycle. On the other hand, seat covers made only of polyester-based fiber fabric are also commercially available, but they lack a high-class feel. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Patent No. 5685003 [Patent Document 2] Patent No. 6118174 [Patent Document 3] International Publication No. 2013 / 125653 Summary of the Invention [Problem to be solved by the invention]
[0012] In view of the above-mentioned state of the prior art, the problem to be solved by the present invention is to provide a recyclable covering material which combines a good feel, high abrasion resistance and a luxurious appearance. [Means for solving the problem]
[0013] The present inventors conducted intensive research and repeated experiments in order to solve the above-mentioned problems, and as a result, unexpectedly found that a skin material having the following characteristics could solve the above-mentioned problems, which led to the completion of the present invention. That is, the present invention is as follows.
[0014] [1] A skin material in which a skin layer and a base layer which is a sheet-like material having a polyester-based fibrous material as a skeleton are attached via an adhesive layer which is a polyester-based resin, The epidermis layer has the following characteristics (1) to (8): (1) The skin layer is composed of at least one type of main fiber and a thermoplastic resin having a melting point that is 20° C. or more and 170° C. or less lower than the melting point of the main fiber; (2) The fineness of the main fiber is 0.01 dtex or more and 0.5 dtex or less; (3) At least a portion of the thermoplastic resin bonds the main fibers; (4) At least a portion of the thermoplastic resin is exposed on the outer surface of the outer surface fiber layer in a chunk form; (5) When the thermoplastic resin is observed from the surface, the average projected area of the block shape is 1.3×10 ―9 m 2 Below is; (6) The main fiber is a polyester fiber; (7) The thermoplastic resin is a polyester-based resin; and (8) The surface other than the outer surface of the skin layer faces the adhesive layer; The skin material is an artificial leather having an outer surface fiber layer having the above structure. [2] The skin material according to [1] above, wherein the outer surface fiber layer of the skin layer is intertwined with a scrim layer which is a woven fabric. [3] The skin material according to [2] above, wherein the woven or knitted fabric of the scrim layer is a polyester-based fiber. [4] The number average volume of the thermoplastic resin of the outer surface fiber layer of the skin layer is 5000 μm 3 More than 14000μm 3 The skin material according to any one of the above [1] to [3], which is as follows: [5] The volumetric density of the thermoplastic resin of the outer surface fiber layer of the skin layer is 1.1 × 10 12 pieces / m 3 Above 3.0×10 12 pieces / m 3 The skin material according to any one of the above [1] to [4], which is as follows: [6] The skin material according to any one of [1] to [5] above, wherein the skin layer is printed or embossed. [7] The skin material according to any one of [1] to [6] above, wherein the adhesive layer has a dot pattern or a mesh and mosaic pattern. [8] The skin material according to any one of [1] to [7] above, wherein the adhesive layer is derived from a polyester-based hot melt powder resin adhesive. [9] The skin material according to any one of the above [1] to [8], wherein the base material layer is a woven fabric, a knitted fabric, a nonwoven fabric or a felt.
[10] The basis weight of the base material layer is 20 g / m 2 ~800g / m 2 The skin material according to any one of the above [1] to [9],
[11] The skin material according to any one of [1] to
[10] above, which has a plurality of through holes penetrating in the thickness direction.
[12] A seat covering material comprising the covering material according to any one of [1] to
[11] above.
[13] A vehicle seat cover comprising the covering material according to any one of [1] to
[11] above. Effect of the Invention
[0015] The skin material according to the present invention has a good feel, high abrasion resistance, and a luxurious appearance, and is also highly recyclable because the skin layer, adhesive layer, and base material are all made of polyester fibers or polyester resins. Therefore, the skin material according to the present invention can be suitably used not only as a material for car interiors, but also in fields such as seat skins and interior materials for railway cars, aircraft, ships, etc., vehicle seat covers, clothing, shoes, bags, smartphone cases, interior items, and furniture. [Brief description of the drawings]
[0016] [Figure 1] FIG. 11 is a diagram showing another example of the state of lump resin in the outer surface fiber layer of the skin layer. [Diagram 2] FIG. 11 is a diagram showing another example of the state of lump resin in the outer surface fibrous layer of the skin layer. [Diagram 3]FIG. 11 is a diagram showing another example of the state of lump resin in the outer surface fibrous layer of the skin layer. [Figure 4] FIG. 11 is a diagram showing another example of the state of lump resin in the outer surface fibrous layer of the skin layer. [Diagram 5] FIG. 11 is a diagram showing another example of the state of lump resin in the outer surface fibrous layer of the skin layer. [Figure 6] FIG. 11 is a diagram showing another example of the state of lump resin in the outer surface fibrous layer of the skin layer. [Figure 7] FIG. 11 is a diagram showing another example of the state of lump resin in the outer surface fibrous layer of the skin layer. [Figure 8] FIG. 11 is a diagram showing another example of the state of lump resin in the outer surface fibrous layer of the skin layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, an embodiment of the present invention will be described in detail. One embodiment of the present invention is a skin material in which a skin layer and a base layer which is a sheet-like material having a polyester-based fibrous material as a skeleton are attached via an adhesive layer which is a polyester-based resin, The epidermis layer has the following characteristics (1) to (8): (1) The skin layer is composed of at least one type of main fiber and a thermoplastic resin having a melting point that is 20° C. or more and 170° C. or less lower than the melting point of the main fiber; (2) The fineness of the main fiber is 0.01 dtex or more and 0.5 dtex or less; (3) At least a portion of the thermoplastic resin bonds the main fibers; (4) At least a portion of the thermoplastic resin is exposed on the outer surface of the outer surface fiber layer in a chunk form; (5) When the thermoplastic resin is observed from the surface, the average projected area of the block shape is 1.3×10 ―9 m 2 Below is; (6) The main fiber is a polyester fiber; (7) The thermoplastic resin is a polyester-based resin; and (8) The surface other than the outer surface of the skin layer faces the adhesive layer; The skin material is an artificial leather having an outer surface fiber layer having the above-mentioned structure.
[0018] The main fibers contained in the outer surface fiber layer of the skin layer of the artificial leather are fibers contained in an amount of 60% by mass or more relative to 100% by mass of the outer surface fiber layer. More preferably, the amount is 70% by mass or more, and even more preferably, 80% by mass or more. There is no particular upper limit, but the amount may be 99% by mass or less. The main fiber contained in the outer surface fiber layer is a polyester fiber from the viewpoints of strength, ease of manufacturing ultrafine fibers, general market availability, etc., and as described above, in consideration of applications requiring durability such as the field of car seats, polyethylene terephthalate is preferred because the fiber itself does not yellow even when exposed to direct sunlight for a long period of time and has excellent color fastness. Furthermore, from the viewpoint of reducing the environmental load, chemically recycled or material recycled polyethylene terephthalate, or polyethylene terephthalate using plant-derived raw materials is even more preferred.
[0019] Suitable polyester fibers as the main fibers constituting the outer surface fiber layer include polyethylene terephthalate (PET), polytrimethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polylactate, copolymers thereof, etc. These fibers may be used alone, or fibers of various polymers may be mixed in any ratio.
[0020] If not only the main fibers but also the thermoplastic resin contained in the outer surface fiber layer described below, as well as the scrim, adhesive layer, and base material layer, are made of a polyester-based resin, then it is possible to, for example, collect used PET from clothing or beverage bottles, process this into recycled PET resin, and use this to manufacture a skin material, and then recycle the used (end-of-life) skin material to, for example, process it into insulation material or filter material, and then recover PET from the used insulation material or filter material, thereby producing a recyclable skin material that is suitable for a circular economy.
[0021] The main fiber has a fineness of 0.5 dtex or less, more preferably 0.35 dtex or less, and even more preferably 0.2 dtex or less, from the viewpoints of production efficiency, production stability, and abrasion resistance during fiber production, the fineness is 0.01 dtex or more, and even more preferably 0.03 dtex or more. The subject fiber may be a fiber directly spun by a melt spinning method, a fiber obtained by a wet spinning method, or an ultrafine fiber obtained by removing the sea part from a sea-island fiber in which a copolymer polyester is used as the sea part and a regular polyester is used as the island part.
[0022] The main fiber may contain or have attached thereto additives, such as titanium oxide, various antioxidants, light fasteners, antistatic agents, flame retardants, softeners, fastness improvers, pigments such as carbon black, dyes, etc., as long as the desired effect is achieved.
[0023] When a method using staple fibers is selected as the method for producing the main fibers, the staple fiber length is preferably 13 mm to 102 mm, more preferably 25 mm to 76 mm, and even more preferably 38 mm to 76 mm in dry methods (carding method, airlaid method, etc.), and is preferably 1 mm to 30 mm, more preferably 2 mm to 25 mm, and even more preferably 3 mm to 20 mm in wet methods (papermaking method, etc.). For example, the aspect ratio (L / D), which is the ratio of length (L) to diameter (D) of staple fibers used in wet methods (papermaking method, etc.), is preferably 500 to 2000, more preferably 700 to 1500. Such an aspect ratio is preferable because the short fibers have good dispersibility and openability in the slurry when the short fibers are dispersed in water to prepare a slurry, the fiber layer strength is good, and the fibers are shorter and easier to disperse as single fibers than in the dry method, so that the fibers are less likely to have a fluffy ball-like appearance called pilling due to friction. For example, the fiber length of a short fiber having a diameter of 4 μm is preferably 2 mm or more and 8 mm or less, more preferably 3 mm or more and 6 mm or less.
[0024] The thermoplastic resin constituting the outer surface fiber layer and having a melting point 20° C. to 170° C. lower than the melting point of the main fiber is a polyester-based resin. Suitable polyester-based resins include polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polylactate, and copolymers thereof.
[0025] The thermoplastic resin does not necessarily have to be composed of only a single polymer, and may be a mixture of multiple types of polymers. In addition, this thermoplastic resin may contain or have attached thereto additives, such as titanium oxide, various antioxidants, light resistance agents, antistatic agents, flame retardants, softeners, fastness improvers, pigments such as carbon black, dyes, etc., as long as the desired effect is achieved. The thermoplastic resin has a melting point that is 20°C to 170°C lower than the melting point of the main fiber, and when there are two or more types of main fiber, it is necessary that the melting point is 20°C to 170°C lower than the melting point of the main fiber having the lowest melting point. When the thermoplastic resin is a mixture of multiple types of polymers, it is necessary that the thermoplastic resin having the highest melting point has a melting point that is 20°C to 170°C lower than the melting point of the main fiber having the lowest melting point. Regarding the melting point range, the abrasion resistance and appearance quality described in the present application can be achieved within the above range, but from the viewpoint of maintaining particularly good appearance quality, the melting point of the thermoplastic resin is preferably 40°C to 150°C lower, more preferably 40°C to 100°C lower than the melting point of the main fiber.
[0026] The melting point in this specification refers to a value measured by DSC (differential scanning calorimeter). The difference in heat between the measurement sample and the reference material is measured by the differential scanning calorimeter, and the melting point of the measurement sample is calculated. Specifically, the peak top of the endothermic peak observed when the temperature is raised from 25°C to 250°C at 10°C / min is taken as the melting point.
[0027] The thermoplastic resin must be exposed in a lump form on the outer surface of the outer surface fiber layer. If it is not exposed on the surface, the main fibers present on the surface are not sufficiently held by the resin fusion, and the fibers are prone to fall off or break, so the skin layer does not have sufficient abrasion resistance. In addition, part or all of the thermoplastic resin bonds the main fibers together. If the thermoplastic resin does not bond the main fibers together, the main fibers are not sufficiently held together, and the fibers are prone to fall off or break, so the skin layer does not have sufficient abrasion resistance or strength.
[0028] The thermoplastic resin is also present in the cross section of the outer surface fiber layer in a block shape. If the thermoplastic resin is present only on the surface and not in a block shape in the cross section, the main fibers are not sufficiently held by the resin fusion, and the skin layer does not have sufficient abrasion resistance. In addition, the density of the outer surface fiber layer does not increase sufficiently, and the skin layer cannot express the luxurious, moist texture characteristic of the skin layer.
[0029] In this embodiment, the thermoplastic resin bonds the main fibers together and has a number average volume of 5000 μm 3 More than 14000μm 3 The number average volume of the thermoplastic resin is preferably 14,000 μm or less. 3 If the number average volume exceeds 5000 μm, the proportion of the same thermoplastic resin bonding multiple main fibers becomes high, which tends to cause the material to feel rough to the touch and makes it difficult to achieve a satisfactory sense of luxury as a skin layer. 3 If the number average volume is less than 5,500 μm, the particle size will not be large enough to surround one main fiber, the main fiber will not be effectively held, and the abrasion resistance required for car interiors will not be achieved. 3 More than 13000μm 3 Less than or equal to 5500 μm, more preferably 3 More than 12000μm 3 The following is the result.
[0030] In the outer surface fiber layer, the volumetric number density, which is the number of thermoplastic resin particles per unit volume, is 1.1 x 10 12pieces / m 3 Above 3.0×10 12 pieces / m 3 It is preferable that the number of particles per unit volume of the thermoplastic resin is 1.1×10 or less. 12 pieces / m 3 If the volume number density of the thermoplastic resin is less than 3.0×10, a plurality of main fibers cannot be bonded with a plurality of thermoplastic resins, and the fiber bundles fall off when worn, and sufficient wear resistance cannot be exhibited. 12 pieces / m 3 If the volume density of the thermoplastic resin exceeds 1.1×10, the first surface fiber layer becomes too hard and the soft and luxurious feel required for the skin layer cannot be obtained. 12 pieces / m 3 Above 2.0×10 12 pieces / m 3 Less than or equal to 1.1×10 12 pieces / m 3 More than 1.6 x 10 12 pieces / m 3 is less than or equal to
[0031] The average projected area of the block-shaped thermoplastic resin when observing the outer surface fiber layer from the surface was 1.3 × 10 -9 m 2 More preferably, it is 1.1×10 or less. -9 m 2 The average projected area is 1.3×10 -9 m 2 If it is larger than this, there is a drawback that the resin agglomerates present on the surface relative to the main fibers are large, impairing the quality of appearance and the feel. In addition, there is a drawback that the density of the fusion points between the main fibers is reduced, and the main fibers are not sufficiently held together, resulting in poor abrasion resistance of the surface layer. On the other hand, from the viewpoint that it is desirable for the resin agglomerates to be large enough to bond the main fibers together, the average projected area should be 0.001×10 -9 m 2 It is preferable that the value is equal to or larger than 0.01×10 -9 m 2 That's all.
[0032] It is preferable that the thermoplastic resin bonds the main fibers isotropically when viewed from any angle in three dimensions. Specifically, it is preferable that the average value of the quotient obtained by dividing the major axis by the minor axis when the thermoplastic resin in the surface fiber layer is approximated as an ellipse is 100 or less. If the average value of the quotient obtained by dividing the major axis by the minor axis when the thermoplastic resin is approximated as an ellipse is 100 or less, the heat-sealing resin is sufficiently melted when bonding the main fibers, and the adhesive strength is high and high abrasion resistance can be obtained. The average value of the quotient obtained by dividing the major axis by the minor axis when the thermoplastic resin is approximated as an ellipse is more preferably 10 or less, and even more preferably 5 or less. Since it is preferable that the thermoplastic resin is close to a true sphere (quotient value 1), it is not particularly limited, but the average value of the quotient obtained by dividing the major axis by the minor axis when the thermoplastic resin is approximated as an ellipse may be 1 or more.
[0033] The above thermoplastic resins can be evaluated by cutting the surface layer vertically and observing it with an optical microscope or an electron microscope, or by measuring three-dimensional images with CT or MRI. It is necessary to accurately evaluate the position, density, shape, and size of the heat-sealed resin not only on the surface of the surface fiber layer but also inside it, and this can be accurately evaluated by performing continuous image analysis of the cross section in X-ray CT as described in the examples, taking the steps to properly process the images, and then performing mathematical analysis.
[0034] The artificial leather constituting the surface layer can use a scrim layer as a core material. When using a scrim layer, it is preferable that the scrim layer used is a woven fabric or a knitted fabric from the viewpoint of stabilizing the production of the papermaking sheet in the papermaking process and increasing the mechanical strength of the obtained outer surface fiber layer. The material of the scrim layer is preferably the same polymer system as the main fiber in terms of color uniformity in dyeing, and in the case of knitted fabric, a single knit knitted with a gauge of 22 to 28 is preferable. In the case of woven fabric, it is more preferable because it can achieve higher dimensional stability and strength than knitted fabric. The yarn constituting the woven fabric may be a monofilament or a multifilament. The single fiber fineness of the yarn is preferably 5.5 dtex or less in terms of easily obtaining a soft surface layer using an entangled sheet. As the form of the yarn constituting the woven fabric, it is preferable to use raw silk of a polyester resin multifilament, or a processed yarn subjected to a false twist process, which is twisted with a twist number of 0 to 3000 T / m. The multifilament may be a normal one, and for example, polyester 33 dtex / 6f, 55 dtex / 24f, 83 dtex / 36f, 83 dtex / 72f, 110 dtex / 36f, 110 dtex / 48f, 167 dtex / 36f, 166 dtex / 48f, etc. are preferably used. The yarns constituting the woven fabric may be long multifilament fibers. In order to obtain a skin layer that is soft and has excellent mechanical strength, the weaving density of the yarns in the woven fabric is preferably 30 yarns / inch or more and 150 yarns / inch or less, more preferably 40 yarns / inch or more and 100 yarns / inch or less. In order to provide good mechanical strength and an appropriate feel, the weight of the woven fabric is 20 g / m 2 More than 150g / m 2 The following are preferred. The presence or absence of false twist processing in the woven fabric, the number of twists, the single fiber fineness of the multifilament, the weaving density, and the like contribute to the entanglement with the constituent fibers of the main fiber layer, the flexibility of the skin layer, as well as to mechanical properties such as seam strength, tear strength, tensile strength / elongation, and stretchability, and may be appropriately selected depending on the target physical properties and applications.
[0035] In the skin layer, the outer surface fiber layer is arranged so as to be the front side of the skin material. For example, when the artificial leather that becomes the skin layer is composed of an outer surface fiber layer and a scrim layer, the first surface (upper surface) of the outer skin layer becomes the front surface (front side), and the back surface of the scrim layer becomes the second surface (lower surface). In addition, when the skin layer of this embodiment is composed of three layers, that is, an outer surface fiber layer / scrim layer / back surface fiber layer, the back surface of the back surface fiber layer becomes the second surface. In the case where the artificial leather has a structure of outer surface fiber layer / scrim layer / back surface fiber layer, the material constituting the back surface fiber layer is not particularly limited, but from the viewpoint of exhibiting good recyclability, it is preferable that the material is the same as the main fiber and / or thermoplastic resin of the outer surface fiber layer. In addition, when the back surface fiber layer is included, it may be made of a material different from that of the outer surface fiber layer, for example, by adding a flame retardant, so as to add desired properties.
[0036] Methods for forming the outer surface fiber layer include using the main fibers and / or heat-fusible fibers in the form of short fibers and entangling the fibers to form a nonwoven structure using a papermaking method, a carding method, an air-laying method, or the like. From the viewpoints of uniform dispersion of the constituent fibers and ease of use of ultrafine fibers, it is particularly preferred that the surface fiber layer be formed by a papermaking method.
[0037] In addition, in this embodiment, the layers can be entangled using a hydroentanglement method called a spunlace method, a needle punch method, or the like, but the hydroentanglement method is preferred because it does not destroy the structure of the woven or knitted fabric that is the scrim layer.
[0038] The surface of the outer surface fiber layer obtained by the above method is raised and dyed to be used as a suede-like or nubuck-like surface layer. The raising treatment can be performed by a known method such as buffing with sandpaper. In this case, if the raising treatment is performed before the heat-fusible fibers of the surface fiber layer are heat-fusible, a suede-like surface texture can be obtained. On the other hand, if the raising treatment is performed after the heat-fusible fibers are heat-fusible, a nubuck-like surface texture can be obtained.
[0039] The dyeing process is not particularly limited. For example, when the main fiber is a polyester fiber, a disperse dye is generally used. The dyeing method can be a conventional method well known to dyeing processors, and a liquid flow dyeing machine is preferably used for the surface layer in terms of uniform dyeing. The surface layer thus dyed is reduced and washed by soaping or in the presence of a chemical reducing agent to remove excess dye. The conditions for the reduction and washing are not particularly limited, and may be selected according to the chemical stability of the main fiber and the thermoplastic resin, and a basic reducing agent or an acidic reducing agent may be used without any particular limitation according to conventional methods.
[0040] The thickness of the skin layer is preferably 0.40 mm to 1.50 mm. By making the thickness of the skin layer within the range of 0.40 mm to 1.50 mm, the thickness of the ultrafine fiber layer can be sufficiently ensured while the number of fusion points per unit area and the entanglement between the fibers in the ultrafine fiber layer on the surface can be sufficiently maintained, so that a soft feel and sufficient stretchability can be achieved at the same time.
[0041] The weight of the skin layer is 100g / m 2 ~400g / m 2 It is preferable that the basis weight is 100 g / m 2 ~400g / m 2 By so doing, it is possible to achieve both a soft feel and a moderate hardness. The basis weight is preferably 200 g / m 2 ~300g / m 2 It is.
[0042] In order to have good abrasion resistance when used as a surface layer, it is preferable that the surface layer is one in which the scrim is not exposed when the surface is abraded with a pressure load of 12 kPa in accordance with JIS-L-1096 E method (Martindale method) less than 50,000 abrasions.
[0043] The surface layer preferably exhibits flame retardancy of Class 4 or higher in a flammability test conforming to the U.S. Federal Motor Vehicle Safety Standard "FMVSS No. 302." By maintaining flame retardancy of Class 4 or higher, it is possible to clear the flammability standards used in automobiles, aircraft, and other applications, thereby expanding the range of applications that can be applied when used as a surface layer.
[0044] The adhesive used to form the adhesive layer must be a polyester-based resin, and examples of the polyester-based resin that can be used preferably include polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polylactate, and copolymers thereof.
[0045] The polyester resin used in the adhesive does not necessarily have to be composed of a single polymer, and may be a mixture of multiple types of polymers. In addition, the thermoplastic resin may contain or have attached thereto additives, such as titanium oxide, various antioxidants, light stabilizers, and flame retardants, as long as the desired effect is achieved.
[0046] The form of the adhesive is not particularly limited, and may be in the form of an emulsion, slurry, gel, liquid, solid, tape, nonwoven fabric, etc. In the solid form, a powder form is preferred from the viewpoint of processability, and the particle size of the powder polyester resin is preferably 50 μm to 900 μm. Even if the adhesive is in the form of a nonwoven fabric before bonding, it may no longer be in the form of a nonwoven fabric after bonding.
[0047] Furthermore, the adhesive may be applied in any shape for adhering the surface layer and the base layer, but is preferably in the shape of a dot, a mesh, or a mosaic pattern. By applying the adhesive in dots or partially and then heat welding, it is possible to ensure proper breathability, and compared to the case of using the conventional frame lamination method, it is possible to suppress the generation of unpleasant odors and mold, and maintain a hygienic environment.
[0048] The means for applying the adhesive is not particularly limited. Examples include sinter coating, powder dot coating, curtain flow coating, film coating (a sheet-shaped adhesive is sandwiched between objects and melted and bonded by applying heat and pressure), and spray coating. The adhesive used may be in the form of powder or liquid, and may be of any suitable type. It is preferable to use powder dot coating. Another method that can be used is to sandwich an adhesive processed into a spider web (mesh) film between objects and melt-bond them by applying heat and pressure.
[0049] The basis weight of the adhesive layer (amount of coating per unit area) is not particularly limited, but is preferably 10 g / m 2 More than 100g / m 2 Less than 15 g / m 2 More than 95g / m 2 More preferably, 20 g / m 2 More than 90g / m 2 The basis weight may be 10 g / m or less. 2 If it is less than 100g / m, the adhesion will be insufficient and the covering material will easily peel off during use. 2 If this occurs, the possibility of resin seeping out during processing increases, making the product more likely to be defective.
[0050] The base layer of this embodiment is a sheet-like material having a fibrous skeleton. The resin used for the fabric of the base layer must be a polyester-based resin. As the polyester-based resin, polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polylactate, copolymers thereof, etc. are preferably used.
[0051] The polyester resin used in the sheet-like material having the fibrous material as the skeleton of the base layer does not necessarily have to be composed of only a single polymer, and may be a mixture of multiple types of polymers. In addition, the polyester resin may contain or have attached thereto additives, such as titanium oxide, various antioxidants, light fasteners, antistatic agents, flame retardants, softeners, fastness improvers, pigments such as carbon black, and dyes, as long as the desired effect is achieved.
[0052] The form of the sheet-like material having a fibrous skeleton used in the base layer is not particularly limited, and may be woven, knitted, nonwoven, felt, etc. From the viewpoint of increasing the mechanical strength of the skin material, the fabric used is preferably woven or knitted. From the viewpoint of easy control of stretchability and three-dimensional shape, knitted fabric is more preferable.
[0053] The basis weight of the fabric used in the base layer is not particularly limited, but is not particularly limited, and is preferably 20 g / m 2 More than 800g / m 2 Less than 30 g / m 2 More than 700g / m 2 More preferably, 40 g / m 2 More than 600g / m 2 The basis weight may be 10 g / m or less. 2 If the thickness is less than 800g / m, the mechanical strength of the skin material becomes insufficient. 2 Anything above this is undesirable from an economic standpoint.
[0054] At least one surface of the skin layer and one surface of the adhesive layer must be bonded together. The shape of the adhesive layer when bonded is not particularly limited, but as described above, it is preferable that the adhesive layer has any one of a dot shape, a mesh shape, and a mosaic pattern shape.
[0055] The adhesive layer must be bonded to the base layer. The shape of the adhesive layer when bonded is not particularly limited, but as described above, it is preferable that the adhesive layer has any one of a dot shape, a mesh shape, and a mosaic pattern shape.
[0056] The skin material of this embodiment may have a plurality of through holes penetrating in the thickness direction. From the viewpoints of breathability and design, it is preferable to provide a plurality of through holes by perforation. The shape of the through holes in the skin material in a plan view is not particularly limited, and may be a circle, an ellipse, a polygon, a star, an irregular shape, or the like.
[0057] The surface layer of the present embodiment may be printed or embossed. A printed pattern or an embossed design on the surface layer can give a more luxurious feel. EXAMPLES
[0058] First, the methods for measuring various physical properties used in the examples will be described below. (1) Average projected area of resin chunks One hundred images were taken of 100 randomly selected points on the surface of the sample at a magnification of 250 times using a scanning electron microscope. The areas of 100 points of the lump resin were calculated using each image, and the average was used as the average projected area of the lump resin.
[0059] The images were taken using a scanning electron microscope JSM-5610 manufactured by JEOL Ltd. ImageJ was used as image processing software to calculate the area of the resin aggregates. The area was calculated by outlining the resin aggregates in the 250x image and converting the outline to the scale of the captured image. The outlined area was 0.001 x 10 -9 m 2 The average area of 100 resin chunks is 0.1 x 10 -9 m 2 The less than 100 digits have been rounded off. The lump resin was selected based on the criteria that the lump resin bonded the main fibers and was exposed on the outer surface of the surface fiber layer.
[0060] (2) Explanation of heat-sealing point structure The state of lump resin and how to judge it will be explained with reference to the figures. Fig. 1 is an example where the resin is exposed on the outer surface of the outer surface fiber layer but the main fibers are not bonded together, and Fig. 2 is an example where the resin is exposed on the surface and the main fibers are bonded together. Fig. 3 is an example where the resin is not exposed on the surface but the main fibers are bonded together, Fig. 4 is an example where the resin is exposed on the surface and the main fibers are bonded together, and Fig. 5 is an example where the resin is exposed on the surface but the main fibers are not bonded together. Fig. 6 is an example where the heat-fusible fiber is not melted, and is not called lump resin. Fig. 7 is an example where sheath-core fiber is used as the heat-fusible fiber, and the heat-fusible fiber retains its fibrous shape, and is not called lump resin. Fig. 8 is an example where the resin is exposed on the surface but the main fibers are not bonded together. In the figures, 1 is the main fiber, 2 is lump resin, 3 is unmelted resin, and 4 is sheath-core fiber. Here, "the main fibers are bonded to each other" means that at least two main fibers penetrate the interior of the block resin (thermoplastic resin) and are physically bonded to each other.
[0061] (3) Number average volume (μm 3 ), volumetric density (10 12 pieces / m 3 ) [Image measurement using X-ray CT] The observation of the mass of the heat fusion point was performed using an X-ray CT device (Rigaku Corporation's "High Resolution 3D X-ray Microscope Nano3DX"), observing the entire thickness direction of the outer surface fiber layer of the epidermis layer, and taking 3D images with the center of the thickness direction cross section as the center point of the observation area. The image measurement was performed using copper as the X-ray target, with an X-ray tube voltage of 40 kV, a tube current of 30 mA, an exposure time of 12 seconds per image, and a spatial resolution of 1.08 μm / pixel. Using the same operation, 1000 images were taken per 180 degrees of rotation angle, and 3D measurement data was obtained.
[0062] [Image processing method, analysis method, and method for calculating the average value of the quotient obtained by dividing the major axis by the minor axis when approximating an ellipse] The detailed process of processing and analyzing the 3D measurement data obtained above is described below. The image analysis software used was ImageJ (version: 1.51j8, National Institutes of Health, USA). (i: Image rotation) The three-dimensional image is rotated so that the plane direction of the outer surface fiber layer coincides with the plane direction consisting of the xz axes, and the thickness direction of the outer surface fiber layer coincides with the y axis. (ii: Trimming) Trim the 3D image into a rectangular parallelepiped. In this case, the y-axis is set to a range that includes the entire thickness and does not include excessive space outside the membrane. Regarding the x-axis and z-axis, after determining the range of the y-axis, the maximum range is taken so that no pixels outside the measurement field of view are included within the trimmed rectangular parallelepiped. (iii: Setting the axes) The number of pixels in the x-axis direction of the cropped image is set to x0, the number of pixels in the y-axis direction to y0, and the number of pixels in the z-axis direction to z0. (iv: Filtering) A median filter is applied with a radius of 2 pix. (v: Region division) The Otsu method is used to divide the regions. At this time, in order to clearly distinguish between light and dark, the pixel brightness value is set to 0 for the air portion that does not include the outer surface fiber layer and 255 for the main fiber portion that constitutes the outer surface fiber layer. (vi: Segmentation) The image processing method segmentation is applied to pixels with a brightness value of 255. Structures with a number of pixels (pix) of 10,000 or less that are connected three-dimensionally into a single region with a brightness value of 255 are considered noise, and their brightness values are changed to 0 to remove them. (vii: Noise Removal) Among pixels with a luminance value of 0, pixels with a luminance value of 0 that are three-dimensionally surrounded by pixels with a luminance value of 255 are regarded as noise, and their luminance values are changed to 255 and removed. (viii: Calculation of porosity) A two-dimensional image of the xz plane is cut out from the three-dimensional image at a thickness of 1 pix in the thickness direction, and the porosity on that plane is calculated using the following formula: Porosity = Number of pixels with brightness value 0 / Total number of pixels and calculate it. (ix: Thickness distribution of porosity) The above (viii) is carried out for all y data to obtain the distribution of porosity in the y-axis direction. (x: Calculation of the size of high-brightness pixels) The size of pixels with a luminance value of 255 is obtained by the Thickness method. As a result, a three-dimensional image is obtained in which the value of the diameter of the largest sphere that can fit into each pixel becomes the luminance value. The Thickness method is the method described in the literature "A new method for the model-independent assessment of thickness in three-dimensional images" by T. Hildebrand and P. Rueesgsegger, J. of Microscopy, 185 (1996) 67-75, and can be executed, for example, by Thickness of BoneJ, a plug-in of image analysis software ImageJ. Further, for the image obtained here, since structures of 12 μm or less are regarded as main fibers and excluded from the analysis target, the luminance values of pixels with a luminance value less than or equal to the number of pixels corresponding to 12 μm are changed to 0. (xi: Binarization) For the image obtained in (x) above, all pixels with a luminance value other than 0 are set to 255, and pixels with a luminance value of 0 are left as 0, and binarization is performed. (xii: Particle analysis) Three-dimensional particle analysis is performed on the image obtained in (xi) above. A three-dimensionally continuous portion with a luminance value of 255 is regarded as one particle, and the center coordinates (XC, YC, ZC) of each particle and the number of pixels of the continuous structure are calculated. (xiii: Definition of surface, skim layer, and back surface) In the data of the porosity distribution obtained in (ix) above, since 95% of the range is used for analysis (the outermost surfaces of the surface and the back surface are excluded from the analysis), on the surface of the outer surface fiber layer, the value of the y-axis farthest from the front side where the porosity is 0.95 or more is defined as y1. When a skim layer is included, the numerical value of the porosity in (viii) and the portion where fibers with a fineness of 100 dtex or more appear are defined as the front end, and its coordinate is set as y2. (xiv: Calculation of the total number of pixels and data analysis) For all the particles obtained in (xii) above whose coordinate values satisfy y1 < YC < y2, the number of particles and the total number of pixels of the particles are obtained. Number average volume (μm 3 ) = Total number of pixels of particles * p * p * p ÷ Number of particles Volume density (10 12 pieces / m 3 ) = number of particles÷(|y2-y1|*p*x0*p*z0*p) Here, p is the pixel size (m / pix), which is the actual size (m) of one pixel (pix). (xv: Calculation of the average value of the quotient obtained by dividing the major axis by the minor axis when approximating an ellipse and data analysis) A three-dimensional particle analysis is performed on the image obtained in (xi) above. A three-dimensional continuous part with a brightness value of 255 is considered to be one particle, and each particle is approximated as an elliptical sphere. The three axes of the elliptical sphere are the major axis, the middle axis, and the minor axis in descending order. The average value of the quotient obtained by dividing the major axis by the minor axis when approximating each particle as an ellipse is calculated using the following formula: Quotient obtained by dividing the major axis by the minor axis (thermoplastic resin major axis / minor axis ratio) = major axis length / minor axis length The measured value was calculated as the arithmetic average of 30 measurement points. However, if the major axis of the approximated ellipsoid is greater than the minimum axis of the rectangular parallelepiped being analyzed, it is excluded as an error and the aspect ratio is set to 0. The average aspect ratio is calculated using the following formula: Average major axis divided by minor axis = sum of major axis divided by minor axis of particles ÷ (total number of particles - total number of particles excluded) The calculation was done as follows.
[0063] (4) Fineness Ten randomly selected points on the front or back of the outer surface fiber layer of the epidermis layer were photographed with a microscope at a magnification of 2500 times, and the diameters of the fibers at 50 points were measured and the average value was calculated as the average fiber diameter. The fineness [dtex] of the main fiber was calculated by converting the obtained average fiber diameter and the density of the main fiber. In addition, the outer surface fiber layer of the epidermis was immersed in ethanol and wrapped in a gelatin capsule, which was then freeze-dried in liquid nitrogen. The capsule was then cut with a knife and the cut cross section of the sample, which had been returned to room temperature, was observed using a scanning electron microscope (JSM-5610, manufactured by JEOL Ltd.) at WD = 10 mm and a magnification of 200x. The thickness of the woven yarns constituting the scrim layer was measured at five points on each of the 20 images obtained, and the fineness of the woven yarns constituting the scrim layer was determined by measuring the thickness of the woven yarns constituting the scrim layer. The fineness of the heat-fused fiber is the fineness of the raw fiber, and was evaluated using a scanning electron microscope. Specifically, an adhesive carbon tape was attached on the evaluation stage, 0.05 g of the raw short fiber was placed on it, and the excess heat-fused fiber was removed with an air duster to obtain a sample. The sample was observed under the conditions of WD = 10 mm and magnification 200 times, and the thickness was measured at five points on each of the 20 images obtained.
[0064] (5) Abrasion resistance and wear loss The sample surface was abraded with a pressure load of 12 kPa using the method specified in JIS-L-1096 E method (Martindale method). The evaluation criteria for this test method were the number of abrasions until the sample surface layer was abraded and the scrim or adhesive layer was exposed, and the evaluation was divided into the following evaluation criteria (grades). (Evaluation Criteria) XX: After 5,000 abrasion cycles, significant fiber loss occurred and evaluation was not possible. ×: The scrim is exposed after less than 30,000 abrasion cycles. △: The scrim is exposed after 30,000 or more and less than 40,000 abrasion cycles. ◯: The scrim is exposed after 40,000 or more and less than 50,000 abrasion cycles. ◎: The scrim is exposed after 50,000 or more abrasion cycles. In addition, a sample (40 mm diameter, perfect circle) of the outer surface fiber layer of the skin layer, as specified in JIS-L-1096 E method (Martindale method), was abraded 50,000 times with a pressure load of 12 kPa, and the weight change [mg] was evaluated as the abrasion loss. The measurement was performed three times, and the average was used as the result.
[0065] [Example] Polyethylene terephthalate fibers with a single fiber fineness of 0.15 dtex and a melting point of 255°C were produced by the direct spinning method and cut to a length of 5 mm to form the main fiber. Fully meltable type heat-fusible fibers (Casven 8000 manufactured by Unitika Ltd.) made of polyethylene terephthalate copolymer with a melting point of 180°C, with a single fiber fineness of 1.1 dtex and a length of 5 mm were used as the heat-fusible fibers. These short fibers were dispersed in water at a weight ratio of main fiber:heat-fusible yarn = 90:10 to prepare a slurry. This slurry was then paper-formed to produce a fiber mass of 110 g / m 2 A papermaking sheet for surface fiber was produced. Also, polyethylene terephthalate fibers with a single fiber fineness of 0.15 dtex and a melting point of 255°C were produced by the direct spinning method, and cut to a length of 5 mm to form the main fiber. As the heat-fusible fiber, a fully melted type heat-fusible fiber (Casven 8000 manufactured by Unitika Ltd.) with a single fiber fineness of 1.1 dtex and a length of 5 mm, made of a polyethylene terephthalate copolymer with a melting point of 180°C, was used. These short fibers were dispersed in water at a weight ratio of main fiber:heat-fusible fiber = 97:3 to prepare a slurry. From this slurry, a papermaking method was used to produce a fiber mass of 50 g / m 2 The two layers were made of polyethylene terephthalate fiber with a basis weight of 100 g / m2 and a weave density of 120 (threads / 2.54 cm) in the MD and CD directions. 2 The resulting three-layer laminate was entangled by spraying a high-speed water jet from a straight-flow jet nozzle, and then dried at 130°C for 5 minutes using an air-through dryer to obtain a three-layer nonwoven fabric.
[0066] The surface of the outer surface fiber layer of the obtained nonwoven fabric was buffed with 400 mesh sandpaper to give a nap treatment, and then the nonwoven fabric was placed in a biaxial stretching tester X4HDHT manufactured by Toyo Seiki Seisakusho Co., Ltd., with the shrinkage rate of 5% in each direction, and the center and four corners of both sides were fixed with compressed air grips. The nonwoven fabric was then thermally annealed at 190°C for 5 minutes in a chamber to obtain a skin layer. Next, the fabric was dyed at 130°C using a blue disperse dye (BlueFBL: manufactured by Sumitomo Chemical Co., Ltd.) in a liquid jet dyeing machine, and reduced and washed at 80°C to obtain a suede-like skin layer. The resin aggregates observed from the surface bonded the main fibers as shown in Figure 2, and the average area of the resin aggregates was 1.0×10 -9 m 2 The number-average volume of the thermoplastic resin measured by X-ray CT is 108,000 μm 3 , the volume density is 1.1×10 12 pieces / m 3 The abrasion resistance was 50,000 times, the scrim was not exposed, and the abrasion loss was 18 mg.
[0067] The sum of the weave density in the MD and CD directions is 240 (threads / 2.54 cm), and the fabric is made of 166 dtex / 48 f polyethylene terephthalate fibers with a basis weight of 200 g / m 2 The fabric was used as the base layer fabric, polyester resin powder was applied in dots on the fabric, and the skin layer was then placed on top and bonded while applying heat and pressure using a flat press to obtain a skin material. The resulting skin material has a good texture, high abrasion resistance, and a luxurious appearance, and is also highly recyclable because it is made of polyester resin. [Industrial Applicability]
[0068] The skin material of the present invention has a good texture, high abrasion resistance, and a luxurious appearance. In addition, the skin material of the present invention has excellent recyclability because the skin layer, adhesive layer, and substrate are all made of polyester fibers or polyester resins and do not contain other polymers such as polyurethane. Therefore, the skin material of the present invention can be suitably used in fields such as seat skins and interior materials for railway vehicles, aircraft, ships, etc., vehicle seat covers, clothing, shoes, bags, smartphone cases, interiors, and furniture, in addition to car interior materials. [Explanation of symbols]
[0069] 1. Main fiber 2. Lump Resin 3 Unmelted resin (thermal bonding fiber) 4. Sheath-core fibers
Claims
1. A skin material in which a skin layer and a base layer which is a sheet-like material having a polyester-based fibrous material as a skeleton are attached to each other via an adhesive layer which is a polyester-based resin, The epidermis layer has the following characteristics (1) to (8): (1) The skin layer is composed of at least one type of main fiber and a thermoplastic resin having a melting point that is 20° C. or more and 170° C. or less lower than the melting point of the main fiber; (2) The fineness of the main fiber is 0.01 dtex or more and 0.5 dtex or less; (3) At least a part of the thermoplastic resin bonds the main fibers; (4) At least a portion of the thermoplastic resin is exposed in a chunk form on the outer surface of the outer surface fiber layer; (5) When the thermoplastic resin is observed from the surface, the average projected area of the block shape is 1.3 × 10 ―9 m 2 Below is the result: (6) The main fiber is a polyester fiber; (7) The thermoplastic resin is a polyester-based resin; and (8) The surface other than the outer surface of the skin layer faces the adhesive layer; The skin material is an artificial leather having an outer surface fiber layer having the above structure.
2. The skin material according to claim 1 , wherein the outer surface fibrous layer of the skin layer is intertwined with a scrim layer which is a woven or knitted fabric.
3. The skin material according to claim 2 , wherein the woven or knitted fabric of the scrim layer is a polyester fiber.
4. The number average volume of the thermoplastic resin of the outer surface fiber layer of the skin layer is 5000 μm 3 14000 μm or more 3 The skin material according to any one of claims 1 to 3, wherein:
5. The volume number density of the thermoplastic resin of the outer surface fiber layer of the skin layer is 1.1 × 10 12 pieces / m 3 Above 3.0 x 10 12 pieces / m 3 The skin material according to any one of claims 1 to 3, wherein:
6. The skin material according to any one of claims 1 to 3, wherein the skin layer is printed or embossed.
7. The skin material according to any one of claims 1 to 3, wherein the adhesive layer has a dot pattern or a mesh and mosaic pattern.
8. The skin material according to any one of claims 1 to 3, wherein the adhesive layer is derived from a polyester-based hot melt powder resin adhesive.
9. The skin material according to any one of claims 1 to 3, wherein the base material layer is a woven fabric, a knitted fabric, a nonwoven fabric or a felt.
10. The weight of the base material layer is 20 g / m 2 ~800g / m 2 The skin material according to any one of claims 1 to 3,
11. The skin material according to any one of claims 1 to 3, wherein the skin material has a plurality of through holes penetrating in a thickness direction.
12. A seat covering material comprising the covering material according to any one of claims 1 to 3.
13. A vehicle seat cover comprising the covering material according to any one of claims 1 to 3.
Citation Information
Patent Citations
Extensible joint of bridge
JP1981085003A
Charge detecting circuit
JP1986018174A
Interior finish skin material and interior molding using same
WO2013125653A1
Cited By
Polyester resin composition, artificial leather, and method for producing the same
JP7872635B1